Project Delay Factor Ranking among Contractor, Client and Project Management Consultant in Construction Industry - Asmi, Ade; Djamaris, Aurino RA (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2021)
A construction project delay can result in financial losses to various parties involved both to the Contractor, Client and Project Management Consultant (PMC). This paper presents the results of a survey questionnaire conducted among Contractors, Clients and PMC. Data was analyzed with statistical tools to rank factors that influenced construction delays. From the results of the analysis there were 58 project delay factors that affected the delay of construction projects based on previous research. The project delay factors ranked so as to produce a project delay ranking sequence. Project delay factors will be grouped based on the perception of the Contractor, Client and PMC. Each project delay factor will be analyzed based on the type of delay factor, namely: Finance; Technical; and Coordination. It is concluded that the type of delay factor